Human Rights and Dignity Behind Bars: A Reflection on Death and Dying in World Prisons. (January 2017) - Maschi, Tina; Richter, Marina
Death and dying in prisons constitute a topic of growing importance across the globe. Based on the contributions made in this special issue, we reflect on current debates and outline recommendations for dialogue and practice. Scientific dialogue across the Atlantic, and across the globe, provides insights into different national carceral systems and their ways of dealing with end of life behind bars. At the same time, the comparison also helps to identify basic needs and practices that can work in various settings. We identify several issues where further efforts need to be taken to deepen the dialogue. A common ground for all advancement of legislation and practice constitute the minimal level of rights to which every human being is entitled.